Florida’s urban soils: underfoot yet overlooked (2010)
Approximately 90% of Florida residents—some 16.5 millioninhabitants—live in urban areas. ??is ongoing urbandevelopment results in the conversion of agricultural lands,watersheds, and natural areas into a highly modi?ed urbanand suburban landscape. Florida’s cities, too, have increaseddramatically in size and density in recent decades.??e environmental e?ects of urbanization have, for themost part, been well documented. One area that hasreceived considerably less attention, however, is urbansoils. Indeed, alterations to soils represent one of the leastobvious e?ects of urbanization, but these changes will havefar-reaching consequences. While healthy soils are key toagricultural and forest productivity in rural areas, mosturbanites (save the occasional backyard gardener, water-shed manager, or soil scientist) are unaware of the manyecosystem functions provided by soils in urban watershedsand landscapes. ??us, a more complete understanding ofthe role of soils in the urban environment, as well as thee?ects of urbanization on soils, is essential if we are tosustainably manage the urban soil resource